Performance improvers in cardio-pulmonary resuscitation: a qualitative study - Keivan Babaei; Faezeh Ghesmati; Amir Hossein Nowzari; Afshin Goodarzi (BMC Emergency Medicine)
Abstract Introduction In-hospital cardiac arrest is a critical event, and while cardiopulmonary resuscitation (CPR) is the primary intervention, human factors significantly influence its quality. Traditional quantitative studies often fail to capture the impact of resuscitation team members’ operational and emotional experiences. To address this gap, this qualitative study uses a pragmatist approach to explore the factors that improve the performance of resuscitation team members in emergency departments. Methods A qualitative content analysis was conducted in Western Iran from January /2024 to July /2024, to explore factors improving the performance of resuscitation team members. Participants included 25 nurses and physicians from in-hospital resuscitation teams, selected through purposive sampling. Data was collected through in-depth, semi-structured interviews. Graneheim and Lundman’s systematic approach was employed to analyze the data and uncover latent and manifest content. Results The mean age of participants was 34 years (range 24–51 years), and most held a bachelor’s degree in nursing (48%). The collected data were categorized into a theme titled " latent enhancers " and three main categories with ten subcategories. These categories and subcategories included Perceived beliefs influencing resuscitation (Positive spiritual feedback, mental simulation, and compassion), organizational catalysts (effective leadership, responsive physical space, fertility of motivation, and fruitful education), and psychological improvers (euphoria, pride in competence, and Hope in the shadow of a surprising successful resuscitation). Conclusion Rescuers’ positive beliefs, effective organizational factors, and Psychological improvers were themes extracted from the experiences of rescuers in our study. Holding psychoanalysis sessions with the to create a positive attitude in rescuers towards the outcomes of resuscitation, as well as empowering resuscitation leaders through training leadership skills, considering organizational incentives for resuscitation team members, suitable physical space, and the use of operational training will be an effective and helpful measure in this regard. Clinical trial number Not applicable.